JURIDICAL ANALYSIS OF CHILDREN CARRYING SHARP WEAPONS IN THE TAURAN ACTION IN BOGOR CITY IS REVIEWED IN LAW NUMBER 35 OF 2014 CONCERNING CHILD PROTECTION - Nazlah Kusumah, Dewi; Gilalo, Jacobus Jopie; Ma’arif, Rizal Syamsul (Fakultas Hukum Universitas Djuanda, 2024)
Children need to be protected from the negative impacts of rapid development, the flow of globalization in the fields of communication and information, advances in science and technology, as well as changes in the style and way of life of some parents which have brought about fundamental social changes in people's lives which have a big impact on values. and child behavior. Deviant behavior or unlawful acts committed by children, among other things, are caused by factors outside the child. The purpose of this research is to analyze the problems that often occur, namely related to children who carry sharp weapons in brawls in the city of Bogor, and are associated with law No. 35 of 2014 concerning Child Protection, and the law regulates the rights of children that need to be protected from criminal acts against children, both committed by children and parents against children. In this study, a normative juridical method is used, namely by using literature studies, laws and legal comparisons. And the data used are primary materials such as laws and secondary legal materials such as books, journals, and articles that discuss children's criminal law and the results of his research are that children who are involved in brawls and carry sharp weapons can be sanctioned under the Law on Child Protection, but there must still be attention to the principle of child protection, and the most important thing is the coaching and rehabilitation of children. And law enforcement must pay attention to the interests of children's rights, and in this case, excessive legal protection. And the conclusion of this study is that the protection of children in cases of brawls must be completed by carrying out rehab and prevention, as well as strengthening the role of parents, the community, and the government in educating children to be good.